Ecosystem functions are related to tree diversity in forests but soil biodiversity in open woodlands and shrublands. (26th October 2021) - Ding, Jingyi; Delgado‐Baquerizo, Manuel; Wang, Jun‐Tao; Eldridge, David J.
Abstract: Millions of trees are expected to be planted in forested and non‐forested ecosystems during the United Nations Decade of Restoration. Trees and soil organisms are known to interact, and are both crucial for maintaining multiple ecosystem functions. However, little is known about how the bidirectional relationships among above‐ and below‐ground diversity and ecosystem functions differ across forested and non‐forested ecosystems. We collected data from 126 sites from humid to arid areas in eastern Australia to explore bidirectional relationships among above‐ground (richness of trees and other plants) and below‐ground (richness of bacteria, fungi, invertebrate, protist) diversity and multiple ecosystem functions (multifunctionality, litter and labile carbon storage, nutrient pools, decomposition, groundstorey plant biomass production, soil stability) in forested (tree cover >10%) and non‐forested (tree cover ≤10%, open woodlands, shrublands) systems. We found that the relative importance of above‐ and below‐ground diversity differed among forested and non‐forested systems. Ecosystem functions, such as litter and labile carbon storage and soil stability, were associated mainly with tree richness in forested systems. By comparison, ecosystem functions of non‐forests were related to the richness of soil organisms. Such bidirectional biodiversity–ecosystem function relationships varied with the target function, and the relationships among ecosystem functions and the relative abundance of species varied with tree and soil taxa. The richness of other plants (i.e. all plants excluding trees) and soil organisms was positively coupled in forests only, but there were no linkages among above‐ and below‐ground diversity and ecosystem functions in non‐forests for groundstorey plant biomass production. Furthermore, increases in aridity and soil pH further weakened the biodiversity–ecosystem function relationships in forested and non‐forested systems, by suppressing above‐ground diversity and bacterial richness, respectively. Synthesis . Our study provides strong empirical evidence that the bidirectional relationships among above‐ and below‐ground diversity and ecosystem functions are highly variable across ecosystem and function types. Moreover, our study demonstrates that soil biodiversity is relatively more important than tree diversity in supporting ecosystem functions in non‐forested systems. This suggests that conservation of soil biodiversity is critical for maintaining the functioning of open woodland and shrubland systems. Abstract : The bidirectional relationships among biodiversity and ecosystem functions are highly variable across ecosystems, with functions positively associated with tree richness in forests, but with soil biodiversity in open woodlands. Such relationships are further weakened by increasing aridity and soil pH. This highlights the importance of conserving soil biodiversity for maintaining the functioning of open woodlands, particularly under predicted drier climates.